Building an Escape Room to Raise Awareness of Bullying and Cyberbullying - Jadán-Guerrero, Janio (2022)
Aggressive conflicts are part of the natural social behavior of students in schools, which can lead to bullying when there is a form of discrimination or abuse of power, either because of their characteristics or their way of life (sexual orientation, gender identity, nationality, immigration status, ethnicity, sex, socioeconomic status, health, disability, religious beliefs, pregnancy, among others). In the face-to-face mode, the aggressors could be identified and in some way the conflicts were mediated by teachers or authorities of the institution. However, since education changed to a virtual modality caused by the global coronavirus pandemic, new forms of aggressive behavior have emerged with cyberbullying. In this new scenario teachers, parents and law enforcement should take an active role in raising awareness about bullying and cyberbullying. The main objective of this paper is to describe a proposal based on gamification strategy to prevent and raise awareness of aggressive behaviors among students in a virtual environment. The study focuses on three objectives: a) to study the use of visual methods based on microlearning and the techniques to engage students; b) to identify game scenarios and strategies to design an interactive Escape Room; and c) to evaluate the design and content with three experts in psychology. The results indicate that the Escape Room is a different alternative to understand the problems derived from Bullying and cyberbullying. In the future, we are planning to carry out an intervention with students from Ecuador and Colombia to evaluate the impact.